2007
DOI: 10.1007/s11104-007-9463-6
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray absorption spectroscopy investigation of speciation and biotransformation of copper in Elsholtzia splendens

Abstract: Elsholtzia splendens is a Cu-tolerant plant growing in copper mine areas in the south of China. In this study, X-ray absorption spectroscopy (XAS) was used to investigate the Cu speciation and biotransformation in E. splendens with 300 μM Cu treatment from 10 days to 60 days. The results showed that 300 μM Cu was phytotoxic to E. spendens. The Cu Kedge X-ray absorption near edge structure (XANES) revealed that most copper in roots, stems and leaves exists as divalent Cu. Cu speciation changed depending on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…For example, in the roots, stems, and leaves of E. splendens (a Cutolerant plant) grown in 300 mM Cu for 10 to 60 d, most Cu was bound to O-containing ligands in the cell wall (Shi et al, 2008). Similarly, Kü pper et al (2009) reported that, in frozen, hydrated shoots of Crassula helmsii grown for 8 d at 10 mM Cu, Cu was bound by O ligands (such as organic acids).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the roots, stems, and leaves of E. splendens (a Cutolerant plant) grown in 300 mM Cu for 10 to 60 d, most Cu was bound to O-containing ligands in the cell wall (Shi et al, 2008). Similarly, Kü pper et al (2009) reported that, in frozen, hydrated shoots of Crassula helmsii grown for 8 d at 10 mM Cu, Cu was bound by O ligands (such as organic acids).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no studies meeting all of these criteria have investigated the speciation of Cu, Ni, or Zn in plant roots. For example, many studies use high and environmentally irrelevant concentrations of metals, particularly for Cu where the higher concentrations are most likely used to increase plant uptake and hence improve the signal-noise ratio within analyses ; the extended x-ray absorption fine structure (EXAFS) analyses of Sahi et al (2007) used 630 mM Cu while those of Shi et al (2008) used 300 mM Cu. In contrast, studies have shown Cu to be toxic at concentrations ,10 mM (Kopittke et al, 2010).…”
mentioning
confidence: 99%
“…In their EXAFS measurements on samples frozen in liquid nitrogen, they found evidence for a Cu(II)-phytochelatin complex involved in transport and an unknown Cu complex involved in Cu storage. A second study using the same sample preparation method (that due to the formation of a gas layer around the sample slows freezing, resulting in ice formation with the risk of membrane damage) investigated the Cu-tolerant Cu-excluder plant Elsholtzia splendens (Shi et al, 2008). Unfortunately, these authors applied very high, physiologically not relevant Cu levels (300 mM) in their nutrient solution in order to force enough Cu into the tissues to get an acceptable signal-noise level in their EXAFS data within the limited synchrotron beam time.…”
Section: Multiple Scatteringmentioning
confidence: 99%
“…Reference spectra were obtained from pure compounds of Cu-citrate, Cu 3 (PO 4 ) 2 and CuS. Spectra were also collected from a Cu-glutathione reference sample which was prepared as described previously (28). A Cu-cysteine reference sample containing 5 mM copper was prepared by adding the appropriate volumes of a 100 mM CuSO 4 solution to a 50 mM cysteine solution.…”
Section: Bacteriamentioning
confidence: 99%
“…The data were analyzed with the WinXAS version 3.1 program as previously described (8,28). The spectra were normalized by fitting first-and second-order polynomial functions to the pre-and postedge regions, respectively.…”
Section: Bacteriamentioning
confidence: 99%